2021
DOI: 10.1111/tri.13840
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on kidney transplantation and the kidney transplant recipient – One year into the pandemic

Abstract: Summary The COVID‐19 pandemic has significantly changed the landscape of kidney transplantation in the United States and worldwide. In addition to adversely impacting allograft and patient survival in postkidney transplant recipients, the current pandemic has affected all aspects of transplant care, including transplant referrals and listing, organ donation rates, organ procurement and shipping, and waitlist mortality. Critical decisions were made during this period by transplant centers and individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 65 publications
0
59
0
7
Order By: Relevance
“…[1] Kidney transplant (KT) recipients is a subset of the population at high risk of severe COVID-19 relate consequences due to comorbidities, consequences of chronic kidney disease (CKD) and the burden of immunosuppressive therapy (IST), which in some subjects include also therapies administered before kidney transplantation to treat glomerulonephritis or underlying autoimmune diseases. [2] Data collected so far reported that transplant recipients were at higher risk of morbidity and mortality compared to the general population [3,4]. Despite the great emphasis on IST reduction to face the potentially lethal consequences of COVID-19, no confirming data supports its beneficial effect in terms of survival or clinical and laboratory manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Kidney transplant (KT) recipients is a subset of the population at high risk of severe COVID-19 relate consequences due to comorbidities, consequences of chronic kidney disease (CKD) and the burden of immunosuppressive therapy (IST), which in some subjects include also therapies administered before kidney transplantation to treat glomerulonephritis or underlying autoimmune diseases. [2] Data collected so far reported that transplant recipients were at higher risk of morbidity and mortality compared to the general population [3,4]. Despite the great emphasis on IST reduction to face the potentially lethal consequences of COVID-19, no confirming data supports its beneficial effect in terms of survival or clinical and laboratory manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…In solid organ transplant recipients at or further than two years post-transplant, Dale et al (2021) found their mortality rate to be 18%, compared to a global mortality rate of 2.2% in the general population [4,5]. Risk factors predisposing renal transplant recipients to COVID-19 are similar to those in the general population, including obesity, advanced age, multiple comorbid conditions, poor overall condition, and pulmonary disease [1]. A recent study by Fishman et al (2020) suggested that progression of COVID-19 in solid organ transplant patients occurred more rapidly, with a greater rate of admission to the ICU overall [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…The review article by Khairallah et al (2021) provides an excellent flow diagram outlining major classifications and conceptualization of management of renal transplant patients who tested positive for COVID-19 [1]. Definitions and recommendations are summarized below in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations